Dropped nucleus following phacoemulsification cataract surgery - Tajunisah, Iqbal; Reddy, S.C. (Malaysian Medical Association, 2007)
Twenty two cases of dropped nucleus following 1,196 phacoemulsification procedures in cataract surgery were examined retrospectively to determine the incidence, predisposing factors and visual outcomes of this dreaded complication. All the cases underwent pars plana vitrectomy and the lens fragments were removed with phacofragmotome, vitrectomy cutter or delivered through limbus. The incidence of dropped nucleus was 1.84%. The predisposing factors were hard cataracts (13.6%), polar cataracts (9.1%), previously vitrectomized eyes (4.5%) and high myopia (4.5%). The final visual outcome was > 6/12 in 10 eyes (45.5%); complications were seen in 5 eyes (22.7%). The interval between initial surgery and vitrectomy, the method of fragment removal and the type of lens implanted, did not influence the final visual outcome.